Heimat Goes Mobile: Hybrid Forms of Home in Literature and Film - Kristy R Boney (Studies in 20th & 21st Century Literature, 2016)
Review of Gabriele Eichmanns and Yvonne Franke, Eds. Heimat Goes Mobile: Hybrid Forms of Home in Literature and Film. Rochester, NY: Cambridge Scholars Publishing, 2013. 224 pp.
Keywords: Heimat; cross-disciplinary; film; genre studies